The Tasawuf Wasathiyah Concept in Central Flow of Industrial Revolution 4.0: (Study on the Thinking of Modern Sufism Hamka and Nasaruddin Umar) - Muvid, Muhamad Basyrul; Aliyah, Nelud Darajaatul (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2020)
The purpose of writing this article is to analyze the concepts and thoughts of Sufism wasathiyah Hamka and Nasaruddin Umar. Such as synergizing between the world-hereafter, outward-inward, sharia-nature, God-human, individual-social, and the task as servants of God on earth in a balanced and proportional manner, which in turn gave birth to moderate humans. This paper uses the literature method by exploring and collecting various books, articles, journals, and other documents related to the themes discussed. Findings: Hamka is an archipelago Muslim intellectual figure known for his scientific productivity, evidenced by various works produced in various disciplines, including modern Sufism. Nasaruddin Umar is also an intellectual figure in the Muslim archipelago known as a professor of interpretation of the Qur'an, who also has ideas in the world of Sufism, with his modern Sufism. Modern Sufism that they both thought of as a form of ideas and movements to integrate the interests of the world and the hereafter, the world is used as a medium to draw closer to God, not away from the world. This moderate concept (tawasuth) later gave birth to a paradigm of a balanced industrial era of industrial revolution (tawazun), proportional (i'tidal), tolerance (tasamuh) which eventually became socially and spiritually pious societies.